2018
DOI: 10.1080/09537104.2018.1445836
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactivity in patients with acute coronary syndrome treated with prasugrel or ticagrelor in comparison to clopidogrel: a retrospective pharmacodynamic analysis

Abstract: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y inhibitor is a mainstay of the prevention of stent thrombosis following percutaneous coronary intervention (PCI). In the 2015 European guidelines for the management of acute coronary syndrome (ACS), prasugrel (PRA) and ticagrelor (TICA) combined with aspirin are recommended as first-line therapy. Clopidogrel (CLO) is recommended as an alternative medication for patients with contradictions to these new drugs. This single-center study analyzed the platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…1,2 Current guidelines of ACS primarily recommend ticagrelor and prasugrel combined with aspirin, leaving clopidogrel solely recommended in patients with contraindications for the novel P2Y12 inhibitors. 3 Both ticagrelor and prasugrel have been shown to provide a significant mortality reduction, including prevention of major adverse cardiac events (MACE). 4,5 These benefits go in hand with increased procedural and nonprocedural bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Current guidelines of ACS primarily recommend ticagrelor and prasugrel combined with aspirin, leaving clopidogrel solely recommended in patients with contraindications for the novel P2Y12 inhibitors. 3 Both ticagrelor and prasugrel have been shown to provide a significant mortality reduction, including prevention of major adverse cardiac events (MACE). 4,5 These benefits go in hand with increased procedural and nonprocedural bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) is the main treatment for acute coronary syndrome, but after the treatment, the patients tend to suffer from secondary damage of myocardia tissues triggered by pathological change such as microthrombus [1]. Platelet activation plays a critical role in thrombosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Therefore, current guidelines of the European Society of Cardiology recommend potent P2Y12 inhibitors as the first-line therapy in patients with ACS leaving clopidogrel merely for patients with contraindications to novel P2Y12 inhibitors. [12][13][14][15] Till date, data investigating long-term mortality between clopidogrel, ticagrelor and prasugrel are sparse. Clinical trials that reported data so far had maximal observation durations of 30 months.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, mortality rates are reduced under ticagrelor and prasugrel treatment 10,11 . Therefore, current guidelines of the European Society of Cardiology recommend potent P2Y12 inhibitors as the first‐line therapy in patients with ACS leaving clopidogrel merely for patients with contraindications to novel P2Y12 inhibitors 12‐15 . Till date, data investigating long‐term mortality between clopidogrel, ticagrelor and prasugrel are sparse.…”
Section: Introductionmentioning
confidence: 99%